Territorializing Aquatic Biodiversity: Local Ecological Knowledge (LEK) and Elasmobranch Distribution in the Kango Estuary (Gabon) - Mbeng Mendene, Teddy Tanguy; Kema Kema, Judicael Regis; Okanga Guay, Marjolaine; Akendengue Aken, Igor; Minko Youri, Mvomo; Nkollo-Kema Kema, Christy Achtone (European Scientific Journal, ESJ, 2025)
Elasmobranchs (sharks and rays) are ecologically and socio-economically important, yet their distribution in Central African estuarine systems remains poorly documented. This study investigated the spatial and seasonal distribution of elasmobranchs in the Komo Estuary (Kango, Gabon) using Local Ecological Knowledge (LEK) derived from semi-structured interviews with 30 artisanal fishers, complemented by participatory mapping and GIS analyses. Four species consistently reported by fishers, Fontitrygon ukpam (F. ukpam), Fontitrygon margaritella (F. margaritella), Carcharhinus leucas (C. leucas), and Sphyrna lewini (S. lewini), were treated as focal because they represented all elasmobranch taxa detected in the system and accounted for 100% of observations. Among them, F. ukpam was the most widespread and frequently cited (40 ± 5% of all mentions, CI: 95%), occurring from the estuary to upstream freshwater zones. F. margaritella represented 20 ± 7% (CI: 95%) of reports and, together with C. leucas (≈10 ± 3%, CI: 95%), was concentrated in warm, saline lower-estuary waters. S. lewini was rarely reported (<5% of occurrences). Although no statistically significant differences were detected between wet- and dry-season assemblages, the dry season exhibited a descriptive tendency toward slightly higher richness. Temperature and salinity emerged as key abiotic drivers, while prey availability, turbidity, and fishing pressure likely modulated species distributions. Spatial analyses highlighted localized aggregation zones not detectable through conventional surveys, demonstrating the value of LEK as a robust spatial dataset. Beyond documenting ecological patterns, fisher knowledge also reflected lived territorialities, linking species ecology to the social appropriation of aquatic environments. This study underscores the dual ecological and geographical relevance of LEK, clarifies species–environment relationships in a data-poor estuarine system, and identifies priority sectors for future monitoring and co-management.